Sudden-onset haemolacria in an adolescent girl. (2nd October 2021) - Akca Caglar, Ayla; Akca, Halise; Kurt, Funda; Akcan Yildiz, Leman; Nalcacioglu, Pinar; Buyukkoc, Onur; Dibek Misirlioglu, Emine
ABSTRACT: Haemolacria, also known as bloody tears, is a physical condition in which a person produces tears partially composed of blood. Multiple disorders can cause haemolacria, including trauma, inflammation, vascular lesions, vicarious menstruation, blood disorders, epistaxis, tumours and psychiatric and systemic disorders. Often, no aetiology is identified. It is usually benign, self-limiting, and the treatment depends on the cause. A 14-year-old girl presented to the paediatric emergency department with sudden onset of bloody tears from both eyes and epistaxis for the first time. A detailed history focusing on aetiological factors was unremarkable. Systemic, ocular, nasal and paranasal examination was also unremarkable. Radiological and laboratory investigations were normal, and the patient was diagnosed with idiopathic haemolacria. High-dose oral vitamin C, prophylactic iron therapy and psychological support were provided as conservative treatment. During regular follow-up, there was a spontaneous reduction in the frequency of symptoms.